Study on Chemical Contamination Problem in Macaroni and Pasta Production Technology - Shermin Divanian; Behrouz Akbari-adergani; Parisa Ziarati (Islamic Azad University, 2016)
This study was done to determine the concentration of heavy metals including Lead (Pb) and Cadmium (Cd) and nutrients element Copper (Cu) and Zinc (Zn) in a simple and whole wheat Macaroni in the valid different supermarkets in Tehran. 254 samples from seven Iranian simple Macaroni, four foreign simple Macaroni, and two Iranian whole wheat macaroni were purchased consecutively in 3 seasons of 2015. Results were determined as mean ± SD of dry weight from three replicates in each test. The samples were analyzed by wet digestion method and standardized international protocols were followed for the preparation of material and analysis of mineral and heavy metals contents and analyzed by Atomic Absorption Spectrophotometer. The mean concentration in milligrams per kilogram of dry matter for Lead, Cadmium, Copper and Zinc were determined. According to the results, the mean contents of Lead in the simple Iranian, imported and Iranian whole wheat Macaroni were 2.897, 3.070 and 0.636, amount of Cadmium were 0.469, 0.620 and 0.920, Copper mean contents were 1.563, 11.866 and 7.085 and finally mean level of Zinc were 16.296, 28.425 and 36.318 mg/kg respectively. The mean concentration of Lead, Cadmium, Copper and Zinc between in whole wheat and simple macaroni samples has a significant difference (P<0/05). The results revealed that the Lead and Cadmium contents in all studied analyzed pasta samples exceeded limits set for them according to the national standard Iran, International Codex and World Health Organization, while Zinc content was lower and Copper content in imported studied brands was slightly higher.